Pensamento simbólico e notação musical - Fortes, Fabricio Pires (2009)
This dissertation s purpose is to characterize the musical notation as a representational system in which a certain kind of symbolic thought works. In this sense, the operations that are made in this notation are understood as signs handling without considering the meaning. Though this characterization confronts the question for the possibility of the symbolic thought, which question may be asked like this: how is it possible to warranty the results correction obtained by the sign s handling without taking care of the meanings? Aiming to offer a solid answer to this question, it was used a Leibniz s notion of blind or symbolic thought or knowledge, and certain associated functions. Based in an exam of three functions that are played by signs, as well as an analysis of traditional musical notation s basic elements this work tried to characterize the musical thought as a kind of formal operation. This can be seen in the western basic musical structure, in which scale and rhythm are comprehended as formal organization s ways in that are present a certain kind of calculus. So the signs in musical notation simply do not play the role of substitute the phonic component, but they make visible some structural aspects of these images. This exhibition is attributed in different senses to others representational systems, as diagrams, some artificial languages and even some alternative musical symbolism, some, called graphism , proposed by some 20th century composers. In this perspective the method used was the comparison among the different representation forms in order to identify the musical notation as an ecthetic representation. Concluding, the musical notation is characterized as a constitutive element of the music itself, and it is not a mere secondary code.